PENGUATAN KINERJA PEGAWAI DITINJAU DARI ASPEK SELF EFFICACY, MOTIVASI DAN KOMITMEN KERJA - Saryadi Saryadi; Istiyawati Rahayu (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Applying of verification System in office (VEDIKA) BPJSK go to the electronic claim at year 2020 needing apreciated of various related parties, one of them hospital. Commitment of various related parties is including support stakeholder, needed to a goals performance determined. Target of this research to give the evidence of empiric of influence self efficacy and motivate to performance through commitment organizational. Method analyse with the test quesionary, and test the hypothesis. intake sampel by survey. This sample in research  80 worker medical record. Result of research show the 1) self efficacy and motivation have an effect on positive significance on commitmentorganization; and 2) self efficacy, motivation and commitment organization have an effect on positive significance on performance. F test result show that simultaneously independent variable self efficacy, motivation through commitment organization had a positive significant on performance. R square test result show total R2 = 0,7074%  its meaning variable of performance explained  self efficacy, motivation  on performance  through commitment organization equal 70,74%  so the rest equal to 29,26%  explained a other dissimilar factor outside model of this research.Keywords: self efficacy, motivation, commitment organization, performance